Beliefs as barriers to healthy eating and physical activity. (14th August 2015) - Ross, Anna M.; Melzer, Trish
Abstract: Objectives: Insufficient engagement in healthy eating and physical activity remains a major health concern, significantly contributing to mortality rates worldwide. This study investigated the barriers to, and the psychological factors surrounding, healthy eating and physical activity, as experienced by an under‐researched community sample. Methods: A sample of 741 Australian adults completed an online survey, reporting their physical activity levels, current diet, knowledge of physical activity, and healthy eating recommendations, and the barriers encountered to these health behaviours. Participants also answered questions about self‐efficacy, locus of control, and outcome expectancies in regard to these health behaviours. Results: Increased perception of barriers was found to be associated with decreased participation in both healthy eating and physical activity. Knowledge of nutrition recommendations predicted fruit and vegetable intake, while knowledge of physical activity recommendations did not predict activity levels. Higher self‐efficacy was found in those who engaged in recommended amounts of physical activity, but did not differ between fruit and vegetable consumption groups. Conclusions: Perceived barriers to healthy eating and physical activity affect participation in health behaviours across the population. Negative beliefs surrounding time, cost, effort, and expected outcomes, as well as procedural knowledge to carry out health behaviours, need to be addressed to facilitate health behaviours. Implications: These findings are relevant to inform health promotion and lifestyle interventions to better equip individuals with the information and skills required to overcome the barriers preventing these health behaviours.